Pemenuhan Hak Politik Penyandang Disabilitas di Kabupaten Serang - Rohmawati, Cucum; Sumirat, Iin Ratna; Nakdan, Miftahu Jami; Ajis, Mohd Na'eim (Al Ahkam, 2024)
Citizens have rights that must be respected during general elections. Among these rights is the recognition of women's political rights, which is a means of ensuring that people with disabilities have the same opportunities as voters, candidates for the House of Representatives, Regional Representative Board, President or Vice President, Provincial Legislatives Council, etc. provided they meet the requirements outlined in Law No. 7 of 2017. The lack of participation of people with disabilities in politics in Serang Regency hinders women with impairments from exercising their political rights. This article aims to describe the progress in fulfilling the political rights of individuals with disabilities in Serang Regency. The article's subject was selected using a purposeful method during the writing process. The research findings indicate that individuals with disabilities in Serang Regency still face significant barriers in exercising their political rights. The reason for this is that people are unaware of their political rights, which include those of people with disabilities. As a result, there is a common misconception that individuals with disabilities, especially women, are deemed unfit to run for public office or serve as legislative candidates due to perceived physical limitations that hinder their ability to fulfill their responsibilities effectively.